Application of Saccharomyces cerevisiae for nutritional value enhancement in agricultural plants – a review - Csambalik, László; Tóbiás, Andrea (Acta Biologica Szegediensis, 2019)
This review focuses on yeast suspensions applied with the aim to enhance nutritional content of agricultural products. Seventy one publications were studied, and their details summarized in tables, according to the following plant groups: 1/ arable plants, 2/ vegetables, 3/ medicinal and ornamental plants. It was found that the experimental designs in these papers were inconsistent in most cases and, regardless to plant species used, the concentration of yeast extract, time of application, and repetitions of the treatment were fundamentally different, making evaluation of the methodologies difficult. However, all studies agreed in the positive impact of yeast extracts on nutritional parameters. Therefore, it is advisable to perform further studies to clarify the relationship of individual nutritional parameters to spraying dose, timing and repetition of yeast application.